Characterization of staphylococci in urban wastewater treatment plants in Spain, with detection of methicillin resistant Staphylococcus aureus ST398. (May 2016) - Gómez, Paula; Lozano, Carmen; Benito, Daniel; Estepa, Vanesa; Tenorio, Carmen; Zarazaga, Myriam; Torres, Carmen
Abstract: The objective of this study was to determine the prevalence of Staphylococcus in urban wastewater treatment plants (UWTP) of La Rioja (Spain), and to characterize de obtained isolates. 16 wastewater samples (8 influent, 8 effluent) of six UWTPs were seeded on mannitol-salt-agar and oxacillin-resistance-screening-agar-base for staphylococci and methicillin-resistant Staphylococcus aureus recovery. Antimicrobial susceptibility profile was determined for 16 antibiotics and the presence of 35 antimicrobial resistance genes and 14 virulence genes by PCR. S. aureus was typed by spa, agr, and multilocus-sequence-typing, and the presence of immune-evasion-genes cluster was analyzed. Staphylococcus spp. were detected in 13 of 16 tested wastewater samples (81%), although the number of CFU/mL decreased after treatment. 40 staphylococci were recovered (1–5/sample), and 8 of them were identified as S. aureus being typed as (number of strains): spa -t011/ agr -II/ST398 (1), spa -t002/ agr -II/ST5 (2), spa -t3262/ agr -II/ST5 (1), spa -t605/ agr -II/ST126 (3), and spa -t878/ agr -III/ST2849 (1). S. aureus ST398 strain was methicillin-resistant and showed a multidrug resistance phenotype. Virulence genes tst, etd, sea, sec, seg, sei, sem, sen, seo, and seu, were detected among S. aureus and only ST5 strains showed genes of immune evasion cluster. Thirty-two coagulase-negative Staphylococcus of 12 different species were recovered (number of strains): Staphylococcus equorum (7), Staphylococcus vitulinus (4), Staphylococcus lentus (4), Staphylococcus sciuri (4), Staphylococcus fleurettii (2), Staphylococcus haemolyticus (2), Staphylococcus hominis (2), Staphylococcus saprophyticus (2), Staphylococcus succinus (2), Staphylococcus capitis (1), Staphylococcus cohnii (1), and Staphylococcus epidermidis (1). Five presented a multidrug resistance phenotype. The following resistance and virulence genes were found: mecA, lnu (A), vga (A), tet (K), erm (C), msr (A)/(B), mph (C), tst, and sem . We found that Staphylococcus spp. are normal contaminants of urban wastewater, including different lineages of S. aureus and a high diversity of coagulase-negative species. The presence of multiple resistance and virulence genes, including mecA, in staphylococci of wastewater can be a concern for the public health. Highlights: High prevalence of Staphylococcus spp. in pre- and post-treatment wastewater in UWTPs. First report of MRSA-ST398 in urban wastewater, and of the spa types: t605, t878, and t3262. High diversity of coagulase-negative Staphylococcus species, and high content in resistance genes. Detection of enterotoxin genes in S. aureus and unusual antibiotic resistance genes in coagulase-negative Staphylococcus . Wastewater can contribute to the dissemination of Staphylococcus and their resistance and virulence genes to the environment. Abstract : A high diversity of multidrug-resistant staphylococci with high content in virulence genes were detected in influent and effluent UWTP samples, including the emergent lineage MRSA-ST398.